2007
DOI: 10.1111/j.1872-034x.2007.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated fraction of alpha‐fetoprotein, L3, as a useful prognostic factor in patients with hepatocellular carcinoma with special reference to low concentrations of serum alpha‐fetoprotein

Abstract: The present study indicates that the L3 fraction before treatment serves as a useful prognostic indicator when the serum concentrations of AFP were very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…We previously reported that AFP-L3-positive ([15%) patients had a lower survival rate than negative (\15%) patients in subgroups with a low serum AFP concentration. Moreover, the statistically significant differences were more distinct in the subgroups with lower AFP concentrations [20]. However, the patients in these studies had received various treatments such as hepatectomy, RFA, and transcatheter arterial embolization, and Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We previously reported that AFP-L3-positive ([15%) patients had a lower survival rate than negative (\15%) patients in subgroups with a low serum AFP concentration. Moreover, the statistically significant differences were more distinct in the subgroups with lower AFP concentrations [20]. However, the patients in these studies had received various treatments such as hepatectomy, RFA, and transcatheter arterial embolization, and Fig.…”
Section: Discussionmentioning
confidence: 97%
“…AFP, AFP-L3, and DCP were measured in the same serum before treatment. Cut-off values for positivity for AFP, AFP-L3, and DCP were set at 20 ng/ml, 15%, and 40 mAU/ml, respectively, based on previous studies [18][19][20].…”
Section: Diagnosis Of Hcc and Laboratory Examinationmentioning
confidence: 99%
“…Accordingly, the limited usefulness of AFP-L3 at low AFP concentrations has been reported. On the other hand, Kobayashi et al [29] reported AFP-L3 to be an indicator of an unfavorable prognosis in HCC, even at very low serum AFP concentrations. In addition, Tada et al [30] recently stressed the relationship between AFP-L3 positivity and the pathological features of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Positive findings for such tumor markers have clinical implications for advance warning and appropriate management of patients with HCC [6,7,8,9,10]. In addition, the utility of these three tumor markers for the detection and the evaluation of tumor progression and the prognosis of patients with HCC in comparison to the use of each marker alone has been previously proposed in several reports [11,12,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%